PERCEPÇÃO AMBIENTAL DOS ALUNOS DO ENSINO MÉDIO TÉCNICO: UM ESTUDO NAS ESCOLAS CIDADÃS INTEGRAIS TÉCNICAS EM PATOS, PARAÍBA - Silva, Geymeesson Brito da; Tabosa, Wyllys Abel Farkatt (Geosaberes; Vol 14 (2023), 2023)
Environmental education has become a recurrent theme in studies related to environmental issues, however, its implementation in the curricula of educational institutions has proved to be a complex challenge. Thus, in order to contribute to the treatment of this issue, this study aims to analyze the environmental perception of high school technical students from technical integral citizen schools in the city of Patos-PB. For data collection, an online questionnaire (survey), structured and developed in Google Forms, was used. The diviner data from the research were treated with the aid of the Statistical Package for Social Sciences (SPSS © ) software and analyzed using descriptive statistics, such as frequency, mean and standard deviation. In the results, it was observed that the target audience analyzed is young, most are female, study at ECIT Lynaldo Cavalcanti de Albuquerque, attend the Sales Technician and are enrolled in the 1st year/grade of high school. Therefore, far from ending the discussion on environmental issues, it is believed that this study can theoretically contribute to the literature on environmental education and its possibilities, as well as to the insertion of the theme in the curriculum of technical secondary education.